Sequencing and analysis of the complete mitochondrial genome of Eothenomys eleusis Thomas 1911 from China and its phylogenetic analysis - Liu Zhu; Zhong-Dan Bi; Hong-An Qian; Xiu-Feng Mei; Jing-Yu Zhao; Xin-Xu Zhao; Huan Chen; Jun-Sheng Zhang; Zhong-Wan Piao (Mitochondrial DNA. Part B. Resources, 2023)
The complete mitogenome sequence of Eothenomys eleusis Thomas 1911 was determined using PCR. A circular double-stranded structure makes up the mitochondrial genome of E. eleusis. The complete length of the mitochondrial genome is 16,419 bp. The mitochondrial genome of E. eleusis included 13 protein-coding genes, 1 control region, 22 tRNA genes, 2 rRNA genes and 1 origin of L strand replication. The total base composition of E. eleusis mitochondrial genome was A (32.6%), T (26.3%), G (13.6%) and C (27.5%). We found significant A-T skew in base composition, especially in control regions and protein-coding genes. E. eleusis was supported by bootstrap values of 100%. This study verifies the evolutionary status of E. eleusis in Myodini tribe of Cricetidae at the molecular level. The mitochondrial genome would be a significant supplement for the E. eleusis genetic background.